Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.25122/jml-2020-0101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of 25-OH-Vitamin D and Calcium Deficiency in Adolescent Idiopathic Scoliosis

Abstract: Several etiologies have been proposed as a basis and evolution theory for the development of adolescent idiopathic scoliosis, but limited data were published until now that link vitamin D and calcium deficiency to this condition. The present study aims to evaluate the relationship between 25-OH-Vitamin D, total calcium, and the following data: Cobb angle, age, and patient sex. The seasonal variation for vitamin D will also be taken into consideration. A total of 101 patients with a mean age of 11.61 ± 2.33 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…23 Furthermore, lower levels of vitamin D have been correlated with a higher major curve angle in 2 studies of AIS. 9,24 This is in line with a prospective study that showed vitamin D deficiency predicted greater progression of major curve angle over a 2 year time span, with patients who received vitamin D supplementation compared with placebo having significantly less curve progression. 11 When interpreted in conjunction with our findings, it is possible that patients with vitamin D deficiency develop a curve in the surgical range more quickly.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…23 Furthermore, lower levels of vitamin D have been correlated with a higher major curve angle in 2 studies of AIS. 9,24 This is in line with a prospective study that showed vitamin D deficiency predicted greater progression of major curve angle over a 2 year time span, with patients who received vitamin D supplementation compared with placebo having significantly less curve progression. 11 When interpreted in conjunction with our findings, it is possible that patients with vitamin D deficiency develop a curve in the surgical range more quickly.…”
Section: Discussionsupporting
confidence: 80%
“…AIS patients are noted to have significantly lower 25-hydroxyvitamin D levels when compared with age-matched controls presenting after orthopaedic trauma,10 sports injury,9 or healthy adolescents recruited from the community 23. Furthermore, lower levels of vitamin D have been correlated with a higher major curve angle in 2 studies of AIS 9,24. This is in line with a prospective study that showed vitamin D deficiency predicted greater progression of major curve angle over a 2 year time span, with patients who received vitamin D supplementation compared with placebo having significantly less curve progression 11.…”
Section: Discussionsupporting
confidence: 73%
“…Adolescent idiopathic scoliosis (AIS) has been linked to vitamin D deficiency, which may be due to its regulatory effect in calcium-phosphorus metabolism. [69][70][71][72] Low serum vitamin 25(OH)D and calcium levels are negatively correlated with Cobb measurements. 66,[70][71][72][73][74] Development of AIS has been correlated to abnormal bone metabolism, defective bone qualities including regulation of fibrosis, and poor posture control.…”
Section: Pediatric Spinementioning
confidence: 99%
“…[69][70][71][72] Low serum vitamin 25(OH)D and calcium levels are negatively correlated with Cobb measurements. 66,[70][71][72][73][74] Development of AIS has been correlated to abnormal bone metabolism, defective bone qualities including regulation of fibrosis, and poor posture control. 66,69,72 There is a negative correlation between serum turnover markers including alkaline phosphate, osteocalcin, C-terminal telopeptide of type I collagen, and P1NP and adolescent lumbar BMD in those with AIS.…”
Section: Pediatric Spinementioning
confidence: 99%
“…Pathological conditions such as nonspecific symmetrical non-radiating muscle pain, pathological bone fractures, slipped capital femoral epiphysis, back pain, muscle cramps, and pain during running may suggest insufficient or low vitamin D levels [ 17 ]. Vitamin D was also seen as a risk factor for curvature progression among children with scoliosis [ 18 , 19 ]. According to Perez-Rossello, bone demineralization is associated with a median value of 25-OH-vitamin D of 7 ng/mL [ 20 ].…”
Section: Introductionmentioning
confidence: 99%